ChatGPT and DeepSeek Competition: The Impact of Artificial Intelligence and Blockchain on Global Political Dynamics - Dheni Anugerah Prasetya; Fathurozi; Shealsy Ainunna Mei Pratiwi; Miladia Bidayatin Ni'mah (WISE Pendidikan Indonesia, 2025)
The rapid advancement of artificial intelligence (AI) and blockchain technology has created a new dynamic in global politics. technology have created a new dynamic in global politics. This research investigates the geopolitical impact of the technological competition between ChatGPT, which was developed by OpenAI in the United States, and DeepSeek, an AI model from China. China. These two large language models (LLMs) not only reflect technological advancements, but also act as instruments of power. technology, but also act as instruments of soft power, influencing global discourse and digital sovereignty. influencing global discourse and national digital sovereignty. Using a qualitative descriptive method with a literature-based approach, this research analyzes how competition between these AI systems shapes political narratives, regulatory responses, and the strategic use of blockchain for transpiration. regulatory responses, and the strategic use of blockchain for data transparency and trust. data trust. Findings show that while ChatGPT promotes openness and integration of global markets, DeepSeek emphasizes national control and ideological reinforcement. Blockchain plays a complementary role in strengthening accountability and decentralization, but also raises concerns about surveillance and control. The study concludes that the rivalry between ChatGPT and DeepSeek illustrates a broader digital Cold War, which is urging countries to reassess reliance that urges countries to reassess their technological dependence and political alignment. technology and their political alignments in the digital age.